Impact of fluoroquinolone prophylaxis during neutropenia on bloodstream infection: Data from a surveillance program in 8755 patients receiving high-dose chemotherapy for haematologic malignancies between 2009 and 2014. Issue 1 (July 2018) - Kern, Winfried V.; Weber, Susanne; Dettenkofer, Markus; Kaier, Klaus; Bertz, Hartmut; Behnke, Michael; Weisser, Maja; Götting, Tim; Widmer, Andreas F.; Theilacker, Christian; ,
Summary: Objectives: Antibacterial chemoprophylaxis with fluoroquinolones (FQPx) has been commonly used in cancer patients with neutropenia, but its efficacy has been challenged by the emergence of fluoroquinolone resistance. Methods: The impact of FQPx on bloodstream infections (BSI) during neutropenia after high-dose chemotherapy for haematologic malignancies was evaluated through a multicenter hospital infection surveillance system for the period 2009–2014. Results: Among 8755 patients (4223 allogeneic [allo-] HSCT, 3602 autologous [auto-] HSCT, 930 high-dose chemotherapy for acute leukemia [HDC]), 5302 (61%) had received FQPx. Administration of FQPx was associated with fewer Gram-negative BSI in the overall study cohort patients (4.6% vs. 7.7%, adjusted subdistribution hazard ratio [aSHR] 0.59, 95%CI 0.50–0.70), in patients with HDC (3.7% vs. 9.2%, adjusted subdistribution hazard ratio [aSHR] 0.40, 95%CI 0.22–0.70) and auto-HSCT patients (4% vs. 9%, aSHR 0.43, 95%CI 0.33–0.56). In HDC patients, FQPx was associated with a marked reduction in all-cause mortality during neutropenia (2.3% vs. 7.8%, aSHR 0.30, 95%CI 0.15–0.58). Patients receiving FQPx had significantly more BSIs due to ESBL-positive Enterobacteriacea (0.8 vs. 0.3%, RR 2.2, 95%CI 1.17–4.26). BSIs by MRSA ( n  = 5) and VRE ( n  = 11) were rare in our cohort. Conclusions: As used in the participating centers, FQPx was associated with reduced Gram-negative BSI and improved survival among HDC patients. Among HSCT patients, the benefits were less clear. If adapted to local resistance patterns and patient characteristics, FQPx still may be useful in the management of patients with haematologic malignancies.